2017
DOI: 10.1177/1461444817745320
|View full text |Cite
|
Sign up to set email alerts
|

Children and Minecraft: A survey of children’s digital play

Abstract: Digital games such as Minecraft currently hold a position of significance in the media diets of many children. However, little is known explicitly about just who plays, with whom and how. This article presents the quantitative results of a survey of 753 parents of children aged 3–12 years about their child’s engagement with Minecraft. Our results establish Minecraft as the dominant digital game title played by this age group, particularly on tablet devices. We provide evidence of a marked early gendering of ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 43 publications
2
30
0
Order By: Relevance
“…To this extent, Schneier and Taylor discuss how their research into Minecraft PE often showed a more “spontaneous” play style (2018, p. 15). Other studies have shown that Minecraft is played more alone, with Mavoa et al’s (2017) findings indicating that the most common Minecraft play style among children was solo play in creative mode on tablet devices.…”
Section: Overview/ecologymentioning
confidence: 97%
See 2 more Smart Citations
“…To this extent, Schneier and Taylor discuss how their research into Minecraft PE often showed a more “spontaneous” play style (2018, p. 15). Other studies have shown that Minecraft is played more alone, with Mavoa et al’s (2017) findings indicating that the most common Minecraft play style among children was solo play in creative mode on tablet devices.…”
Section: Overview/ecologymentioning
confidence: 97%
“…While extensive writing on the broader importance of Minecraft as a game and cultural phenomenon exists (Garrelts, 2014), these recent studies are among the only texts to focus on Minecraft on mobile devices. In combination, the two articles underscore the absence of research into mobile Minecraft despite the growing prevalence of Minecraft play on mobile devices (Mavoa et al, 2017).…”
Section: Overview/ecologymentioning
confidence: 99%
See 1 more Smart Citation
“…As has previously been identified in other games such as Minecraft (Dezuanni et al, 2015;Mavoa et al, 2018), all our participants used YouTube as a resource for solving problems and overcoming challenges that were presented in their play. Narrah even described how he used YouTube to install Fortnite on a PC, which was challenging because he had "never downloaded a game like that before.…”
Section: Watching As Playing: Youtube and Livestreaming Paratextsmentioning
confidence: 99%
“…Consequently, in this article, we take a more accurate approach to examine how gender and group-learning conditions (in this case, collaboration and cooperation) affect attitudes and achievements in a virtual social game. The game at the center of our study, Minecraft, successfully defines the sandbox genre and has gained wide acceptance among children recently, especially for its promising social aspect (Mavoa, Carter, & Gibbs, 2017). In addition, like other sandbox games, the core gameplay mechanics in Minecraft is to allow players to create their purpose of the game and to construct new elements in the virtual environment such as reenactments of real-world buildings.…”
Section: Introductionmentioning
confidence: 99%